Effects of health qigong exercise on upper extremity muscle activity, balance function, and quality of life in stroke patients - Yang, Huixin; Li, Baolong; Feng, Lin; Zhang, Zhonglou; Liu, Xiaolei (Frontiers in Neuroscience, 2023)
This study explored the effects of Qigong exercises on upper extremity muscle activity, balance function, and quality of life in stroke patients. A total of 30 stroke patients were randomly allocated to either control group or Qigong group. In the Qigong group, participants completed an intervention of Qigong Baduanjin over 8 weeks. Data on the electromyographic activities of the biceps brachii muscle, triceps brachii muscle, and muscle coordination were obtained using surface electromyography and the co-contraction ratio (CCR). Data on balance were obtained using the PK254P balance function detection system. Quality of life was measured using the brief version of the World Health Organization Quality of Life scale. The results for the Qigong group showed a significant difference in CCR of the triceps brachii muscle (p<0.01). Concerning balance (assessed using the open-eye test), there was a significant decrease (p<0.05) in Y-axis trajectory deviations and the Y-axis speed in the Qigong group. In the closed-eye test, the peripheral area of the Qigong group was significantly lower than that of the control group (p<0.05). Significant differences were also observed in physical health (p<0.05), psychological health (p<0.01), environment (p<0.01), and the total scores for quality of life (p<0.01) in the Qigong group. We conclude that Qigong exercises improve the quality of life in stroke patients and have positive effects on the coordination of limb extremities and balance function.